Factors influencing the attitudes of young Sri Lankan-Australians towards seeking mental healthcare: a national online survey - Chethana Mudunna; Josefine Antoniades; Thach Tran; Jane Fisher (BMC, 2022)
Abstract Background Sri Lankans, as part of the South Asian diaspora, comprise one of the largest migrant groups in Australia. Although few data are available, South Asian migrants appear to experience higher rates of mental health problems, but seek help at lower rates than other migrant groups. Understanding factors that underpin mental health care seeking is necessary to inform mental health promotion strategies, including access to care. The aim was to investigate factors influencing attitudes to seeking care for mental health problems among young Sri Lankan-Australians born in Sri Lanka or in Australia. Methods An anonymous cross- sectional online survey which included the Multiethnic Identity Measure, Perceived Stigma Questionnaire, General Help-Seeking Questionnaire, Attitudes Towards Seeking Professional Psychological Help questionnaire and study specific questions to ascertain sociodemographic characteristics. The survey was advertised on social media and specifically included young adults aged between 18-30, who self-identified as being of Sri Lankan heritage and were living in Australia. Participation was not possible for those that did not have access to the internet. Data were analyzed using bivariable and multivariable statistics. Results Of the 396 people who attempted the survey, 323 provided fully completed data, 2 provided > 50% completed data which were included in the analyses. 71 were excluded because < 50% of the survey was completed. From all participants, 39.70% were born in Australia (SLaus), 54.46% born in Sri Lanka (SLsl) and 5.8% born in other countries. SLsl had more stigmatizing attitudes towards mental illness (p = 0.027) and seeking professional psychological help (p = 0.03). Women, those who had spent more years living in Australia and whose fathers were more highly educated had less stigmatized attitudes toward mental illness and help-seeking. Conclusion Country of birth, family characteristics and gender influence stigma towards mental illness and help-seeking. Public health strategies to promote understanding of mental health problems and seeking mental healthcare are more likely to be effective if they address these factors directly.